2017
DOI: 10.3233/cbm-160662
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in advanced appendiceal cancers

Abstract: BACKGROUND Appendiceal cancer is a rare malignancy. The optimal pathologic classification and prognostic factors for survival and treatment strategies remain poorly understood. OBJECTIVE The aim of this retrospective cohort study was to determine prognostic factors, including markers of systemic inflammation, for survival in a cohort of patients with advanced appendiceal adenocarcinomas. METHODS The study included patients with advanced appendiceal carcinoma that were treated between January 2006 and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In recent years, as a noninvasive detection method, serum biomarkers have attracted more and more attention because of their simple operation and large predictive potential [ 3 ]. Several studies have shown that the systemic immune-inflammation index (SII) is related to the prognosis of malignant tumors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as a noninvasive detection method, serum biomarkers have attracted more and more attention because of their simple operation and large predictive potential [ 3 ]. Several studies have shown that the systemic immune-inflammation index (SII) is related to the prognosis of malignant tumors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In a previous study, for malignant appendiceal tumors, NLR and PLR did not appear to be predictive of OS, but the sample size was also relatively small. 13 Their result demonstrated histological grade was more important than inflammatory markers. Our conclusion is compatible with their study.…”
Section: Discussionmentioning
confidence: 98%
“…Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been identified as inflammation markers, which are also used as prognostic factors in cancer. 11,12 A previous study proposed that NLR and PLR were not predictive of overall survival (OS) in advanced appendiceal carcinoma 13 ; this study combined all malignant appendiceal tumors. However, the prognostic values of NLR and PLR are still unclear in LAMN.…”
Section: Introductionmentioning
confidence: 93%
“…Appendiceal tumors are rare, about 0.9%-1.4% of the tumors are seen during histology diagnosis of resected appendiceal specimens. The age-adjusted incidence is 0.12 cases per one million people per year [ 9 ], it is reported in both genders, however, some authors claim that the majority of patients were female [ 10 , 11 ]. The most common primary appendiceal tumor is carcinoid tumor and it makes up 32-85% while adenocarcinomas (mucinous, signet ring, or non-mucinous) make up 4-20% of the tumors [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the patients in this study with advanced disease were offered adjuvant treatment such as right hemicolectomy, cytoreductive surgery, or chemotherapy. Appendicular carcinoma exhibit a variable spectrum of biological behavior, the patient gender, and tumor pathomorphological are associated with OS (overall survival) in advanced cases of appendiceal carcinoma [ 10 ]. The published reports have shown that elevated pre-management tumor marker levels as CEA, CA 19-9 and CA125, to be associated with higher rates of disease recurrence and reduced survival after complete cytoreductive surgery.…”
Section: Discussionmentioning
confidence: 99%